S50 Once-daily glycopyrronium improves lung function in COPD patients: pooled results of the GLOW1 and GLOW2 studies. (19th November 2012) - Banerji, D; Alagappan, V; Martin, C; He, E; Chen, H; Overend, T
Abstract : Introduction: NVA237 (glycopyrronium) is a safe and effective once-daily inhaled long-acting muscarinic antagonist for the maintenance treatment of COPD. Methods: This pooled analysis of the Glycopyrronium Bromide in COPD Airways Clinical Studies (GLOW1 and 2) assessed the efficacy of glycopyrronium 50µg once daily versus placebo and open-label tiotropium 18µg once daily over 26 to 52 weeks in patients with moderate-to-severe COPD. Glycopyrronium and placebo were delivered via the Breezhaler® device and tiotropium was delivered via the Handihaler® device, in the morning between 8:00–11:00 hours. Analyses included trough forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) at Day 1 and Weeks 12, 26 and 52; 24hour (h) serial spirometry in a subset of patients, and FEV1 area under the curve (AUC). Results: 1888 subjects were randomised, 98.2% analysed (glycopyrronium=1059, tiotropium=267, placebo=528); male: 71.5%, mean age: 63.9 years, mean post-bronchodilator FEV1: 55.5% predicted. All trough FEV1 and FVC values for glycopyrronium and tiotropium were significantly greater than placebo (p<0.001) and glycopyrronium was numerically higher than tiotropium at all time-points (table ). The improvement in FEV1 with glycopyrronium was seen immediately after the first dose on Day 1 (90mL at 5min and 144mL at 15min versus placebo, p<0.001) and sustained throughout the 52 Week period. FEV1 AUC for 0–4h, 0–12h, 0–24h and 12–24h for glycopyrronium was significantly greater than placebo (p<0.05). AUC 0–4h for glycopyrronium was significantly greater than tiotropium on Day 1 and Weeks 12 and 26; all other AUC values for glycoprrronium were numerically higher than tiotropium. Conclusion: Once-daily glycopyrronium provided rapid, sustained and clinically meaningful bronchodilation over 52 weeks with efficacy similar to tiotropium in patients with COPD.